Hate Crime in the News: The Media’s Role in Agenda Setting - Collins, Codey J.; Orr, Douglas A.; Zschau, Toralf (International Journal of Criminology and Sociology, 2021)
Examining the extant literature on hate crimes shows that there has been an evolutionary process of Hate Crime legislation (HC). Similar to other social movements such as civil rights, the hate crime movement also had various waves which eventually lead to the passage of legislation. By and large, however, HC research has focused on victims and offenders of hate crimes as well as motivations of bias. Moreover, less research has been done on the media’s portrayal and coverage of HC. Since the media is a noted influencer in social issues (Culotta, 2002; Quisenberry, 2001), we sought to answer how the news media are reporting incidences of hate crimes – particularly LGBTQ+- and compare them with official crime statistics reported by law enforcement agencies. In order to answer these questions, our research utilized a qualitative content analysis using QSR NVivo 12.0 to identify potential themes and trends which may be overlooked in simple quantitative methods. Our dataset comes from the Hate Crime Index ("ProPublica," 2018), for the month of June 2018. Official FBI data is also utilized for comparison, spanning from 2012 to 2016. Our results suggest that the media reports HC within an overall internal Agenda Setting Orientation. During analysis, two main themes were identified that show the (i) media report both the failures and challenges of law enforcement in dealing with HC issue and, (ii) that media highlights various best practices some agencies engage in. Limitations and future research directions are discussed.